Therapy of Lactobacillus casei Shirota strain Fermented Milk to Rats with High-Cholesterol Diet toward Cholesterol Levels and SOD Activity - Alifiani Nur Rohma; Chanif Mahdi; Aulanni’am Aulanni’am (Chemistry Department, The University of Brawijaya, 2017)
This study aimed to determine the fermented milk of Lactobacillus casei Shirota strain potential on cholesterol levels, SOD activity, LPL enzyme activity, and cardiac histopathology. This study used 25 rats (Rattus novergicus) Wistar strain aged 2-3 months, weighing 150-200 grams. These rats were divided into 5 groups: negative control group, positive control group with high-cholesterol diet for 21 days, and therapy group with 1.0 ; 1.5 ; 2.0 mL/rat/day of fermented milk for 14 days. The analysis methods used in this study are One Way ANOVA and Tukey. The results showed that the fermented milk of Lactobacillus casei Shirota strain had a strong effect on blood cholesterol levels and increasing the SOD activity. This study also showed that the fermented milk of Lactobacillus casei with 2.0 mL/rat/day is the most effective dose to decrease the total cholesterol and increase the SOD activity.